CYTOTOXICITY AND ANTIOXIDANT ACTIVITY OF LEAVES AND STEM BARK EXRTACT OF TERMINALIA SCHIMPERIANA HOSTCH. - A. H. , Mohammed,; E. H., Mshelia; S. K., Hamidu,; L. O., Balogun (IJRDO-Journal of Applied Science, 2021)
The aim of this study was to investigate the antioxidant potential and cytotoxicity of the leaves and stem bark of Teminalia schimperianaplant against brine shrimp. Ethyl acetate, ethanol, acetone hexane and water extracts of leaves and stem bark of the plant were obtained by serial extraction using Soxhlet apparatus. Logit and Probit analysis was used to determined the LC50 values for the cytotoxicity of the various extracts. The results shows that all the extracts are less toxic against the brine shrimp as only extracts giving LC50 values lower than 30 μg/ml  were considered to be cytotoxic. Aqueous extract (stem bark) have low toxicity among the various extracts with LC50values of 843.3 and 828.9 µg/ml for both the logit and probit function while ethanol extract (both leaves and stem bark) showed little toxicity with LC50 ranging between 68.1 and 32.2 µg/ml for the leaves and stem bark respectively. The difference between Logistic and Probit analysis lie in the distribution of error.  Antioxidant activity (DPPH) free radical scavenging activity) result shows that both leaves and bark extract shows better antioxidant activity when compared with reference standard ascorbic acid. They exhibit strong antioxidant DPPH radical scavenging activity with IC50 ranging from 25 to 33.0µg/ml for the leaves and stem bark respectively when compared with reference standard ascorbic acid which is 18.5 µg/ml, regarding the fact that the extract is a mixture of a great number of compounds as opposed to pure ascorbic acid used as standard reference. Aqueous  extract (stem bark) with IC50 value of 25µg/ml has better antioxidant activity among the extracts. It can be deduced that T. Schimperiana is less toxic and has better antioxidant activity when compared with standard ascorbic acid.It is therefore recommend that the drug should be used for medicinal purpose because of its therapeutics effect. Further investigations are needed for chemical characterization of the active compounds and more comprehensive biological assays.